Comprehensive Control of Harmonics across Wide Frequency Domain for Railways in Mixed Operation of AC and DC Locomotives - LONG Lilan; AN Youbin; WU Mingshui; MO Tianzhen (Kongzhi Yu Xinxi Jishu)
The traction power supply system of railways operating with a mix of AC-DC-AC and AC-DC electric locomotives frequently encounters train-traction network resonance due to the presence of harmonic currents across a wide frequency domain. In this study, the harmonic impedance analysis method was applied to establish a circuit model for harmonic impedance in traction networks. The function expression for resonance impedance in traction networks was derived in relation to harmonic frequency and feeding section length. The subsequent analysis focused on the generation mechanism and characteristics of train-traction network resonance, leading to the selection of train-traction network resonance control methods and device installation positions. Furthermore, a comprehensive control approach was proposed to address harmonics across a wide frequency domain in existing traction networks, involving the ground installation of active power filters (APFs) and passive high pass filters (HPFs), along with an engineering design solution for the APF+HPF devices. Simulation verification was conducted based on the traction network of a railway in China. The simulation results show that after adopting this approach, the total distortion rate of harmonic current decreases from 75.29% to 1.58% (APF+second-order HPF filter) and 2.55% (APF+blocking HPF filter), demonstrating the good effect of the proposed approach in controlling harmonics across a wide frequency domain. This method can ensure the safe operation of traction power supply systems by effectively suppressing train-traction network resonance and eliminating its associated hazards..